Comparison of Two Suturing Techniques in Removal of Mandibular 3rd Molar Surgery - Syeda Rabia Rahat Geelani, Tahmasub Faraz Tayyab, Ijaz Ur Rehman, Fatima Khattak, Salman Amin, Zeeshan Aslam Jan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was planned to evaluate the techniques of primary wound closure as well as secondary wound closure after removal of mandibular 3rd molar and the difference of both techniques was assessed in term of swelling, pain, and trismus. Methodology: This randomized clinical trial was conducted in the surgery department a tertiary care hospital of Sargodha, Pakistan. Sample size was 60 patients. Both genders were included and the patients’ age was between 19 to 30years, who presented with the complaint of pain and later on, referred for surgical removal of 3rd molar of mandible were the subject of interest of current study. Using lottery method, patients were divided into two groups. Primary closure technique was used on patients of group 1 and secondary closure technique was used for patients of group 2. The collected data was entered in SPSS version 25.0 and analyzed. Independent sample t test was used to explore the difference between two groups. Results: Facial swelling and trismus was found significantly different in both groups on 3rd and 7th day after surgery (p=.001, P=.001). Conclusion: In Conclusion, secondary wound closure technique is better in terms of pain, facial swelling and trismus than primary wound closure technique in surgical removal of impacted 3rd molar of mandible.